Perancangan Dashboard Monitoring Contract Lifecycle Management pada PT X - Christian Evan Budiawan; Siana Halim (Jurnal Titra, 2022)
This study aims to design a monitoring dashboard that can replace the company's two routine manual reports. These reports were prepared by the business intelligence team manually and reported to the board of directors and other department members bi-weekly. The designed dashboard was constructed using python programming to clean and prepare the data set and Google Data Studio to visualize the data. As a result, the dashboard simplifies the reporting process, minimizing human errors, helping business analysts make decisions, and increasing productivity activities in the company. At the end of this work, the designed dashboard is able to replace the manual processes done by the business intelligence team making processing and visualization time be reduced significantly. The work also enables the business intelligence team who has no prior experience in making the report to be able to use the python code and update the dashboard’s data after being trained for short period amount of time.